2007
DOI: 10.1016/j.cardiores.2007.05.020
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II-activated protein kinase C targets caveolae to inhibit aortic ATP-sensitive potassium channels

Abstract: Objective: The vasoconstrictor angiotensin II (Ang II) acts at G q/11 -coupled receptors to suppress ATP-sensitive potassium (K ATP ) channel activity via activation of protein kinase C (PKC). The aim of this study was to determine the PKC isoforms involved in the Ang II-induced inhibition of aortic K ATP channel activity and to investigate potential mechanisms by which these isoforms specifically target these ion channels.Methods and results: We show that the inhibitory effect of Ang II on pinacidil-evoked wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
51
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(58 citation statements)
references
References 60 publications
7
51
0
Order By: Relevance
“…The variation in relative intensity of these two molecular weight bands in 36 weeks WKY and SHR implies the presence of mixtures of isoforms in their aortic smooth muscle. Indeed, several of the PKC isoforms have similar molecular weights (Ohanian et al, 1996;Shin et al, 2000;Sampson et al, 2007). The present results thus support the interpretation that variations in PKC isozymes underlie the desensitization of TP receptors observed in the SHR aorta.…”
Section: Figuresupporting
confidence: 87%
“…The variation in relative intensity of these two molecular weight bands in 36 weeks WKY and SHR implies the presence of mixtures of isoforms in their aortic smooth muscle. Indeed, several of the PKC isoforms have similar molecular weights (Ohanian et al, 1996;Shin et al, 2000;Sampson et al, 2007). The present results thus support the interpretation that variations in PKC isozymes underlie the desensitization of TP receptors observed in the SHR aorta.…”
Section: Figuresupporting
confidence: 87%
“…15,37 However, the mechanism by which PKC inhibits K ATP channels is unknown. Both PKC-and Kir6.1 are localized in the caveolae of arterial smooth muscles, 16,17 which are specialized microdomains in the plasma membrane and serve to compartmentalize and integrate numerous signaling events. 38 Caveolin-1 is a major integral membrane component of caveolar membranes in vascular smooth muscles.…”
Section: Discussionmentioning
confidence: 99%
“…22,39 Interestingly, both Kir6.1 and PKC-have been reported to coimmunoprecipitate with caveolin-1. 17 This caveolin-1 association could serve to cluster PKC and signaling molecules with K ATP channels, allowing for specific modulation while preventing crosstalk with other pathways. In the present study, we found that caveolae disruption with M␤CD or caveolin-1-specific siRNA prevented not only an inhibitory effect of PKC on K ATP currents but also PKC-induced internalization of K ATP channels, suggesting the functional importance of this compartmentalization.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations